2001
DOI: 10.1081/pdt-100002201
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Formulation Variables and Post-compression Curing on Drug Release from a New Sustained-Release Matrix Material: Polyvinylacetate-Povidone

Abstract: A new commercially available sustained-release matrix material, Kollidon SR, composed of polyvinylacetate and povidone, was evaluated with respect to its ability to modulate the in vitro release of a highly water-soluble model compound, diphenhydramine HCl. Kollidon SR was found to provide a sustained-release effect for the model compound, with certain formulation and processing variables playing an important role in controlling its release kinetics. Formulation variables affecting the release include the leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 16 publications
2
24
0
Order By: Relevance
“…The kinetic data of fenoterol release from its matrix tablets F1 to F7 adopting Kollidon ® SR (Table III) shows that all formulas have a release exponent value (n) less than 0.45 indicating a Fickian (diffusion) release kinetics. This results support the diffusion mechanisms of Kollidon ® SR proposed by both BASF technical information and Shao et al (3).…”
Section: Differential Scanning Calorimetry Studysupporting
confidence: 80%
See 1 more Smart Citation
“…The kinetic data of fenoterol release from its matrix tablets F1 to F7 adopting Kollidon ® SR (Table III) shows that all formulas have a release exponent value (n) less than 0.45 indicating a Fickian (diffusion) release kinetics. This results support the diffusion mechanisms of Kollidon ® SR proposed by both BASF technical information and Shao et al (3).…”
Section: Differential Scanning Calorimetry Studysupporting
confidence: 80%
“…Kollidon ® SR is one of the promising release retarding polymers. It has already been used to delay the release of highly water soluble drugs such as Propranolol HCl and Diphenhydramine HCl (2,3). It shows excellent flowability and can be used as an excipient for direct compression.…”
Section: Introductionmentioning
confidence: 99%
“…When used in the tablet formation, it undergoes little cured during the normal processing conditions and, therefore, affects physical integrity and drug release rate. 11,14 Shao et al also reported that curing after compression is very critical in stabilizing the release Figure 6. SEM photograph of batch P15 after curing.…”
Section: Resultsmentioning
confidence: 99%
“…14 Thus, in order to get a stabilized dissolution pattern of DS and improved physical stability, microspheres were subjected to curing at 60°C for 24…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation